Feminism, Engineering, and Technology: Possibilities and Dilemmas - Zuraina, Ali (Publication Bureau, Sri Guru Teg Bahadur Khalsa College, Anandpur Sahib, Punjab, India, 2022)
The excerpt displayed above connotes that a majority of women are still the "second class" citizens working in male-dominated areas, specifically in engineering and computer sciences. They need to prove their competency in the field when a majority of their male colleagues may find that they are not fit for the job. As a result of the small percentage of women involved in the field, it produces a gapin examining the crux of the matter.